Intermittent Short-Term Infusion vs. Continuous Infusion of Piperacillin: Steady State Concentrations in Porcine Cervical Spine Tissue Evaluated by Microdialysis - Elisabeth Krogsgaard Petersen; Pelle Hanberg; Martin Knudsen; Sara Kousgaard Tøstesen; Andrea René Jørgensen; Kristina Öbrink-Hansen; Kjeld Søballe; Maiken Stilling; Mats Bue (MDPI AG, 2022)
Background: Piperacillin is a central drug in the treatment of Pseudomonas aeruginosa spondylodiscitis. Intermittent short-term infusion (STI) remains standard treatment in most centres, although the application of continuous infusion (CI) has shown promising results in other clinical settings. We aimed to evaluate time above the minimal inhibitory concentration (fT > MIC) of the free fraction of piperacillin in steady state conditions in porcine cervical spine tissue following CI and STI using microdialysis with MIC targets of 4, 8, and 16 <semantics>μ</semantics>g/mL. Methods: 16 female pigs were randomized to receive piperacillin/tazobactam as STI (4/0.5 g every 6 h) or CI (4/0.5 g as a bolus followed by 12/1.5 g) for 18 h. Microdialysis catheters were placed for sampling of piperacillin concentrations from the intervertebral disc, vertebral cancellous bone, paravertebral muscle, and adjacent subcutaneous tissue during the third dosing interval (12-18 h). Blood samples were collected as reference. Results: CI resulted in fT > MIC > 82% across all compartments and targets, except for intervertebral disc (37%) and vertebral cancellous bone (28%) at MIC = 16 <semantics>μ</semantics>g/mL. In Group STI, >72% fT > MIC was reached for MIC = 4 <semantics>μ</semantics>g/mL in all investigated compartments, while for MIC = 16 <semantics>μ</semantics>g/mL only subcutaneous tissue exhibited fT > MIC > 50%. Conclusion: CI of piperacillin resulted in higher fT > MIC compared to STI infusion across the investigated tissues and targets. CI should therefore be considered in spondylodiscitis cases requiring piperacillin treatment.